Understanding of Mathematical Concepts in the Linear Equation with Two Variables: Impact of E-Learning and Blended Learning Using Google Classroom - Huda, Syamsul; Firmansyah, Mu'min; Rinaldi, Achi; Suherman, Suherman; Sugiharta, Iip; Astuti, Dian Widi; Fatimah, Okis; Prasetiyo, Andika Eko (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
Students need an understanding of mathematical concepts provided by educators who have good skills. Educators must also maximize their teaching time so that it requires learning models such as e-learning and blended learning to meet the loss of teaching time due to other activities that must be done by the teacher besides teaching. This study aims to see the impact of blended learning and e-learning on the ability to understand mathematical concepts of students in the material of two-variable linear equations. The method used in this study is the quasi-experiment with the posttest only control design research. Technical analysis uses one way ANOVA. Based on the results of the study, Blended Learning and E-Learning influence understanding mathematical concepts in the two-variable linear equation material, so that it can be used as a knowledge given to students in understanding mathematical concepts.